Does the electrode amplification style matter? A comparison of active and passive EEG system configurations during standing and walking. (3rd December 2020) - Scanlon, Joanna E. M.; Jacobsen, Nadine Svenja Josée; Maack, Marike C.; Debener, Stefan
Abstract: It has been stated that active‐transmission electrodes should improve signal quality in mobile EEG recordings. However, few studies have directly compared active‐ and passive‐transmission electrodes during a mobile task. In this repeated measurement study, we investigated the performance of active and passive signal transmission electrodes with the same amplifier system in their respective typical configurations, during a mobile auditory task. The task was an auditory discrimination (1, 000 vs. 800 Hz; counterbalanced) oddball task using approximately 560 trials (15% targets) for each condition. Eighteen participants performed the auditory oddball task both while standing and walking in an outdoor environment. While walking, there was a significant decrease in P3 amplitude, post‐trial rejection trial numbers, and signal‐to‐noise ratio (SNR). No significant differences were found in signal quality between the two electrode configurations. SNR and P3 amplitude were test‐retest reliable between recordings. We conclude that adequate use of a passive EEG electrode system achieves signal quality equivalent to that of an active system during a mobile task. Abstract : Typical mobile active‐ and passive‐transmission electrode configurations were compared, using an auditory oddball task during both standing and walking. P3 amplitude and signal‐to‐noise ratio were reduced during walking, but no significant differences were observed between the two configurations. SNR, and P3 amplitude were test‐retest reliable between recordings. We conclude that with adequate use, mobile EEG systems using both active‐ and passive‐transmission electrode configurations can record high quality EEG data.